Role of acpA and acpB in Bacillus anthracis capsule accumulation and toxin independent pathogenicity in rabbits. (June 2021) - Sittner, Assa; Bar-David, Elad; Glinert, Itai; Ben-Shmuel, Amir; Schlomovitz, Josef; Levy, Haim; Weiss, Shay
Abstract: The poly- δ- d -glutamic acid capsule of Bacillus anthracis plays a major role in this bacterium pathogenicity. Capsule synthesis relies on a 5 gene operon; capB, C, A, D and E that are regulated by acpA and acpB, that respond to the major virulence regulator – atxA . We took a genetic approach to examine the involvement of acpA and acpB in capsule production in vitro and on B. anthracis virulence in vivo . To complement the effect of the mutations on capsule accumulation in vitro, we applied our toxin independent systemic infection method to study their effects in vivo . We found that though the roles of acpA and axpB are redundant in vitro, deleting acpA had a significant effect on pathogenicity, mainly on the time to death. As expected, deletion of both acpA and acpB resulted in loss of capsule accumulation in vitro and full attenuation in vivo, indicating that capsule production depends exclusively on acpA/B regulation. To identify additional effects of acpA and acpB on pathogenicity via non-capsule related virulence pathways, we bypassed acpA/B regulation by inserting the pagA promotor upstream to the cap operon, diverting regulation directly to atxA . This resulted in restoration of capsule accumulation in vitro and virulence (in intravenous or subcutaneous inoculation) in vivo . To test for additional pXO2-based genes involved in capsule production, we cloned the pagA prom- capA-E into the chromosome of VollumΔpXO2, which restored capsule accumulation. These results indicate that of the pXO2 genes, only capA-E and acpA are required for capsule production. Highlights: AcpA and AcpB were previously shown to regulate Bacillus anthrcis capsule production. acpA and acpB are mutually redundant in regulating capsule biosynthesis in virto and in vivo . acpA plays a prominent role in this regulation. Other than regulating capsule production, acpA or acpB are not involved in any major virulence pathway. acpA, acpB and the CAP operon are the only pXO2 encoded genes necessary for capsule production.